Innovative Marketing Strategies for the Refined Edible Oil Industry: A Multidimensional Approach - Subasini, M.; Rajiv Vignesh, M.; Revathy, R. (Indian Journal of Marketing, 2013)
Indian markets from low-involvement to high-involvement product categories have been experiencing sweeping changes in the past decade. Changing lifestyles, fragmented market segments and consumer preferences, and intense competition from the brands of multinational corporations have made marketing strategies a prerequisite for marketing success. The aim of the study was to formulate marketing strategies for the refined edible oil market. The refined edible oil has got a higher market potential in recent years and so, many new players are entering the market. The study was conducted from three dimensions to frame the marketing strategy. The first dimension is consumers of edible oil, so the consumers’ attitude towards the refined oil, their consumption pattern, factors influencing the decision making in selection of the type and brand of cooking oil, and their expectations with reference to cooking oil were studied. The second dimension is the market of refined oil and the leading players in the market. Hence, the marketing practices followed by the leading players in the market were also analyzed. The third dimension of the study is the product refined cooking oil. The features of the refined cooking oil were also scrutinized.